2010
DOI: 10.1016/j.trstmh.2009.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Argemone mexicana decoction versus artesunate-amodiaquine for the management of malaria in Mali: policy and public-health implications

Abstract: a b s t r a c tA classic way of delaying drug resistance is to use an alternative when possible. We tested the malaria treatment Argemone mexicana decoction (AM), a validated self-prepared traditional medicine made with one widely available plant and safe across wide dose variations. In an attempt to reflect the real situation in the home-based management of malaria in a remote Malian village, 301 patients with presumed uncomplicated malaria (median age 5 years) were randomly assigned to receive AM or artesuna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 14 publications
1
63
0
Order By: Relevance
“…6 Two strategies for HMM were compared in a randomised controlled trial (RCT): AM as first line treatment with artesunate/amodiaquine (As/Aq) as second line ('AM group'); or the standard As/Aq as first line with another artemisinin combination therapy (ACT), arthemeter/lumefantrine, as second line ('ACT group'). 7 Following the usual practice of assessing antimalarial treatments by outcome in the 28 days after diagnosis, we found that progress to severe malaria was 1.9% in children aged ≤5 years in both groups, and 0% among those aged >5years old, so that the incidence of severe malaria was kept to a lower level than reported in comparable studies of HMM. 8 However the AM and ACT groups were very different in terms of parasite clearance.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…6 Two strategies for HMM were compared in a randomised controlled trial (RCT): AM as first line treatment with artesunate/amodiaquine (As/Aq) as second line ('AM group'); or the standard As/Aq as first line with another artemisinin combination therapy (ACT), arthemeter/lumefantrine, as second line ('ACT group'). 7 Following the usual practice of assessing antimalarial treatments by outcome in the 28 days after diagnosis, we found that progress to severe malaria was 1.9% in children aged ≤5 years in both groups, and 0% among those aged >5years old, so that the incidence of severe malaria was kept to a lower level than reported in comparable studies of HMM. 8 However the AM and ACT groups were very different in terms of parasite clearance.…”
Section: Introductionmentioning
confidence: 65%
“…7 In summary, incidence of severe malaria was under 2.5% in both groups. Most of these cases involved severe anaemia.…”
Section: Outcomes At Day 28mentioning
confidence: 82%
See 2 more Smart Citations
“…Parasites which already have resistance to these drugs may be selected for, but it is improbable that any new resistant mutations would develop in this context because the biomass of parasites in the inoculum is low. A strategy for preventing resistance could be to keep ACTs for patients at highest risk of severe malaria (non-immune patients) and to use other medicines for semi-immune patients (aged 5 years and older, in high-transmission areas), who will improve with other treatments[32]. …”
Section: Review Of the Evidence For The Assumptions Underlying Who's mentioning
confidence: 99%